2018
DOI: 10.1016/j.juro.2017.08.081
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Reconstruction of Bulbar Urethral Strictures is Associated with Multiple Interventions, Longer Strictures and More Complex Repairs

Abstract: Urethroplasty delay is common and often associated with symptomatic events managed by repeat urethral manipulations. Endoscopic treatments appear to lengthen strictures and increase the complexity of repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Detailed screening procedure is displayed in the Fig. 1.There were 9 studies (total 2279 patients) contained smokingstricture recurrence univariate analysis information [3,[8][9][10][11][12][13][14][15], 7 studies (total 2074 patients) contained multivariable analysis information [6, 7, 11-13, 16, 17]. Out of 12 involved studies, 11 studies are retrospective cohort studies and only 1 study was prospectively designed.…”
Section: Results 21 Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed screening procedure is displayed in the Fig. 1.There were 9 studies (total 2279 patients) contained smokingstricture recurrence univariate analysis information [3,[8][9][10][11][12][13][14][15], 7 studies (total 2074 patients) contained multivariable analysis information [6, 7, 11-13, 16, 17]. Out of 12 involved studies, 11 studies are retrospective cohort studies and only 1 study was prospectively designed.…”
Section: Results 21 Study Selectionmentioning
confidence: 99%
“…Some risk factors such as the length of stricture and etiology have attracted the attention of urologists, but other factors such as tobacco consumption has not been evaluated carefully [1,3,8,19] This meta-analysis revealed that tobacco consumption can make the chance of stricture recurrence significantly increased based on both univariate and multivariate analysis. In the multivariate analysis stage, the sensitivity analysis result was not exactly stable, this indicated that more multivariate analysis studies and adjusted estimate between smoking and stricture recurrence were required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be associated with the high rate of previously operated patients, and the traumatic etiology of the stricture, both of them being risk factors for therapeutic failure. 22,23 Additionally, our definition of therapeutic failure was defined as any urethral dilation after surgery, which increases the number of patients considered as therapeutic failures. Nonetheless, from a subjective point of view, when applying the USS-PROMS tool on our patients, we found that the mean score for obstructive urinary symptoms was low, that the satisfaction grade of the patients was of 93%, and that all of the patients would recommend the procedure to other patients.…”
Section: Discussionmentioning
confidence: 99%
“…In erfahrenen Händen spielt es keine Rolle, ob zuerst der therapeutische Versuch einer Sachse-Urethrotomie oder gleich der einer primären, offenen Harnröhrenrekonstruktion gewählt wird [3]. Je nach Literatur und Zentrum wird nach mehrmaligen Harnröhrenschlitzungen aber von einer höheren Misserfolgsquote nach sekundärer Harnröhrenplastik berichtet [45]. Zusammenfassend lässt sich sagen, dass gemäss den international publizierten Daten eine Harnröhrenschlitzung nach Sachse nur bei Patienten mit bulbären und kurzstreckigen Strikturen zu empfehlen ist -denn lediglich da besteht die Aussicht auf einen anhaltenden Erfolg mit minimalem Aufwand.…”
Section: Urethrotomieunclassified